Proceedings of the 33rd ACM SIGMOD-SIGACT-SIGART Symposium on Principles of Database Systems 2014
DOI: 10.1145/2594538.2594559
|View full text |Cite
|
Sign up to set email alerts
|

Counting solutions to conjunctive queries

Abstract: Counting the number of answers to conjunctive queries is an intractable problem, formally #P-hard, even over classes of acyclic queries. However, Durand and Mengel have recently introduced the notion of quantified star size that, combined with hypertree decompositions, identifies islands of tractability for the problem. They also wonder whether such a notion precisely characterizes those classes for which the counting problem is tractable. We show that this is the case only for bounded-arity simple queries, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The result has recently been extended to all conjunctive queries over a fixed schema by Chen and Mengel [11]. Structural properties that make the counting problem for CQs tractable in the case where the schema is part of the input have been identified in [16,18]. Join Evaluation.…”
Section: Related Workmentioning
confidence: 99%
“…The result has recently been extended to all conjunctive queries over a fixed schema by Chen and Mengel [11]. Structural properties that make the counting problem for CQs tractable in the case where the schema is part of the input have been identified in [16,18]. Join Evaluation.…”
Section: Related Workmentioning
confidence: 99%
“…There are however some promising recent advances that identify islands of tractability for the allocation problems where at most one good is allocated to each agent: it has been recently shown that those instances where the treewidth of the agents' interaction-graph is bounded by some constant (i.e., have a low degree of cyclicity) can be solved in polynomial-time (Greco et al, 2015). The result is based on recent advances on counting solutions of conjunctive queries with existential variables (Greco & Scarcello, 2014a). Unfortunately, if the structure is quite cyclic this technique cannot be applied to large instances, because its computational complexity has an exponential dependency on the treewidth.…”
Section: Allocation Gamesmentioning
confidence: 99%
“…1, the query Count((X 1 = 3)∧(X 2 = 2)∧(X 3 = 1)) would return 2, as there are 2 instances matching the query condition. We note that the above formulation of counting is a special and simple case of the general counting problem in conjunctive queries, known from database theory [9] (we provide more details in Section 5).…”
Section: Preliminariesmentioning
confidence: 99%
“…Support for counting queries is a primary component in any database management system. In such systems, the query mechanism must support conjunctive queries over multiple tables, and with a variety of possible query predicates [9]. Moreover, the queries are typically executed over tables that cannot be fully materialized in the main memory.…”
Section: Related Workmentioning
confidence: 99%